Terapia comportamental para controle de incontinência urinária de esforço em mulheres idosas: construção e validação de protocolo de intervenções de enfermagem - Santos, Kamyla Félix Oliveira dos (2016)
In recent decades has arisen interest in options of less invasive treatments, low cost and proven efficiency for stress urinary incontinence, such as behavioral therapy. There is currently a variety of care that does not follow a standardized and evidence-based practice. Thus, the need for the development of specific nursing care protocols is justified to improve the quality of care for incontinent elderly women. In order to support the care practice of nurses in the empowerment process of elderly women as behavioral therapy, the Urinary Control Theory was used as the theoretical framework of this study, derived from the Roy’s Adaptation Theory. Objective: To create a protocol of nursing interventions about behavioral therapy for the adaptation process of elderly women with stress urinary incontinence before the urinary control. Method: This is a methodological study. The World Health Organization guided the steps for the protocol creation. Data collection occurred from July 2015 to February 2016. Initially, there was an integrative literature review for selection of clinical guidelines, in addition to nursing interventions and activities proposed by the Nursing Interventions Classification for the control of urinary incontinence. Immediately, there was the synthesis of empirical material and critical and reflexive analysis for the selection of the best clinical evidence. These findings supported the elaboration of the data collection tool to the validation step by expert consensus. This study was appreciated by the Ethics Committee of the Science and Health Center of the Federal University of Paraíba and approved under protocol registration number 0561/15 and CAAE (Presentation Certificate for Ethical Appreciation): 50061015.1.0000.5188. Results: 14 interventions were selected among the best evidences about the behavioral therapy of three international clinical guidelines that were addressed in 11 nursing interventions of the Nursing Interventions Classification. Also, 138 activities were enumerated, proposed by the Nursing Interventions Classification, consensually validated by experts for implementation of nursing interventions. Interventions and eligible Nursing activities were related to four guiding principles of behavioral therapy that include Urinary Control Theory Adaptation modes. In the motivation axis for continence, the behavior and education modification was addressed: individual; in the lifestyle change, weight control and water monitoring; in control of micturition habits, control of urinary elimination, urinary incontinence care, self-care assistance: toilet use, perineum care, bladder retraining and control of medicines; while in the pelvic floor training, exercises for pelvic muscles. Conclusion: The protocol in question generates, in the target-population, a simultaneous adaptive answer between the adaptation modes supported by Urinary Control Theory, supporting important contributions to research, teaching and the Nursing practice, being applicable in Primary Care services, especially in the implementation of permanent education that incorporates technical and scientific material resources to guarantee and an effective nursing care with a view to the management of stress urinary incontinence.